Development of a mathematical model for simultaneous heave, pitch and roll motions of planing vessel in regular waves - Ghadimi, Parviz; Dashtimanesh, Abbas; Djeddi, Seyed Reza; Faghfoor Maghrebi, Yaser (International Journal of Scientific World, 2013)
The market for planing boats has shown steady growth in the recent years and this has caused an increase in the need for designing tools. The need is even more vital for the prediction of seakeeping and maneuverability of planing boats. Although the numerical methods are proved to be useful for the displacement vessels, they seem to be relatively impractical dealing with the complexities of the hydrodynamic behavior of planing boats. In this paper, a simple method for prediction of Heave, Pitch and Roll motions of the planing vessels in regular waves is presented. In the formulation of the present mathematical model, a 2-dimensional technique using momentum theory is applied. Different aspects of the added mass and 2D+t theories are also implemented for the section-based simulations of the planing vessel. The developed method is analyzed through a set of validation tests while the experimental results of the literature are used in order to validate the obtained results. The results are then evaluated in different degrees of freedom and favorable agreement has been achieved against the experimental data.